87.8k views
2 votes
SOMEONE HELP ASAPPPPPPPPP

SOMEONE HELP ASAPPPPPPPPP-example-1
User Roohi Ali
by
5.3k points

2 Answers

3 votes

Answer:

D =
f^(-1)(x) = 4(x+12) =
f^(-1)(x) = 4x+48

Explanation:

First, replace f(x) with y, and switch x and y:


y = (1)/(4)x-12


x = (1)/(4)y-12

Now, solve for y again:


x+12=(1)/(4)y


y = 4(x+12)

Replace y with correct inverse function notation, and you have your answer:


f^(-1)(x) = 4(x+12)

User Zillan
by
5.5k points
5 votes

h(x)= 48x+8 is your answer then dude

User Nicola Di Lillo
by
5.6k points